Variation of compressive strength in colored concrete traces in the city of Teófilo Otoni in the State of Minas Gerais (International Journal of Geoscience, Engineering and Technology, 2020)
This work analyzed the variation of strength and workability of concrete traces with inorganic pigment based on iron oxide with levels varying in 3%, 5% and 6% in the city of Teófilo Otoni- MG. 27 specimens were manufactured, submitted to consistency and compression tests with ages of rupture of 7, 14 and 28 days. Colored concrete is a type of exposed concrete, characterized by dispensing with the application of coatings in buildings. Three strokes T1, T2 and T3 were defined with theoretical compressive strength fck of 18 MPa, 25 MPa and 40 MPa at 28 days respectively. The best results were obtained by the T1P3, T2P3 and T3P3 lines with the addition of 3% pigment in both tests. Significant resistance gains were observed at 7 and 14 days and a reduction at 28 days, at 7 days the gains were about 65% for T1P3, 60% for T2P3 and 82% for T3P3 in relation to theoretical resistance. The colored line that obtained the greatest resistance was T3P3, reaching a fck of 43.09 MPa at 14 days and the worst was T3P6 with 25.97MPa at 28 days. In the slaughter tests it was noted that the best workability was obtained with the addition of 3% being 4.5; 4.2 and 8.3 and it was observed that as the addition content increased, the measure of abatement of the mixture was reduced. The most recommended application for application in colored concrete, whose compressive strength was the closest to the theoretical values and the workability of the mixtures were better.